2013
DOI: 10.7567/jjap.52.07hf13
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study to Produce Multiple Focal Points of Acoustic Field for Active Path Selection of Microbubbles through Multi-bifurcation

Abstract: We previously reported our attempt to propel microbubbles in a flow by a primary Bjerknes force, which is a physical phenomenon where an acoustic wave pushes an obstacle along its direction of propagation. However, when ultrasound was emitted from the surface of the body, controlling bubbles in an against-flow was necessary. It is unpractical to use multiple transducers to produce the same number of focal points because single-element transducers cannot produce more than two focal points. In this study, we int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…We have ever reported our attempts to control MBs using the primary and secondary acoustic force for active control in artificial blood vessels. Recently, we have demonstrated active path selection of MBs by using a matrix array transducer to produce multiple focal points [6]. Also, we have confirmed a dependence of aggregates formation of MBs upon frequencies of ultrasound in static water [7].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…We have ever reported our attempts to control MBs using the primary and secondary acoustic force for active control in artificial blood vessels. Recently, we have demonstrated active path selection of MBs by using a matrix array transducer to produce multiple focal points [6]. Also, we have confirmed a dependence of aggregates formation of MBs upon frequencies of ultrasound in static water [7].…”
Section: Introductionmentioning
confidence: 62%
“…In this study, we investigated controlling the aggregates of BLs in multi-bifurcated flow of artificial blood vessel with multiple focal points of US by making use of aggregates formation. We have previously confirmed that making use of aggregates formation of MBs is effective for controlling MBs in flow to be propelled before entering into an ultrasound field to receive more acoustic radiation force [6][7][8].…”
Section: Introductionmentioning
confidence: 94%
“…The catheter reflects ultrasound in water because its sound speed is 1520-40 m/s and the density is 2 g/cm 3 . The original catheter is transparent and easily bent by hand.…”
Section: A Application Of Cantilever Theory To Thin Cathetermentioning
confidence: 99%
“…The reason of that is considered as the difference in the surface shape of the catheter, where the former was considered as a cylinder, as the latter was a plane, which should be studied in the future research. Figure 9 shows captured images of the microscope when two different continuous ultrasound waves were applied on a thin catheter in the artificial blood vessel, which was made of poly(ethylene glycol) [2][3][4][5][6] and had two bifurcations with minimum inner diameter of 1 mm. Let us notice that the catheter is invisible due to its high transparency, thus the presence of the catheter has to be confirmed by inner diameter, which is visible due to light refraction of air inside.…”
Section: B Investigation Of Frequency Dependency Of Acoustic Radiatimentioning
confidence: 99%
See 1 more Smart Citation